2020
DOI: 10.3390/jcm9113720
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Pancreatic Cancer in Patients with Chronic Pancreatitis

Abstract: Background: Patients with chronic pancreatitis (CP) have an increased risk of developing pancreatic ductal adenocarcinoma (PDAC). We present data on PDAC in one of the most extensive European single-centre cohort studies of patients with CP. Methods: Retrospective analysis of prospectively collected data of patients with CP was performed. Aetiology of CP was determined according to the M-ANNHEIM classification system and only patients with definite CP > 18 years at data analysis were included. The final dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 45 publications
(60 reference statements)
2
33
0
1
Order By: Relevance
“…In recent decades, there is accumulating evidence that longstanding pre-existing chronic pancreatitis is a strong risk factor of developing pancreatic cancer[ 25 ]. Low body mass index and pancreatic exocrine insufficiency in patients with chronic pancreatitis define a high-risk population with latent PDAC[ 136 ]. In comparison with the general population, patients with chronic pancreatitis had a significantly increased risk of pancreatic cancer, especially those with an older age at onset and a > 60 pack-year smoking history[ 137 ].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…In recent decades, there is accumulating evidence that longstanding pre-existing chronic pancreatitis is a strong risk factor of developing pancreatic cancer[ 25 ]. Low body mass index and pancreatic exocrine insufficiency in patients with chronic pancreatitis define a high-risk population with latent PDAC[ 136 ]. In comparison with the general population, patients with chronic pancreatitis had a significantly increased risk of pancreatic cancer, especially those with an older age at onset and a > 60 pack-year smoking history[ 137 ].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…While still debated, multiple studies have shown that fibrosis can play a tumor supportive role, and some have even implicated macrophages in initiating or driving the fibrotic response (Chandler et al, 2019; DeNardo and Ruffell, 2019; Jiang et al, 2016; Zhang et al ., 2021). Fibrotic pathologies have also been linked to a higher risk of developing cancer, such as chronic pancreatitis being a significant risk factor for PDAC (Lowenfels et al, 1993; Vujasinovic et al, 2020). In addition to TRMs driving fibrosis, other studies have implicated TRMs in supporting tumor growth through distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that early onset and prolonged disease was a significant risk factor for CP-related PC. In another European study from Sweden, Vujasinovic et al [ 25 ] evaluated the risk of PC in a retrospective analysis of prospectively collected pancreatic clinical data. In contrast to other studies, they subclassified the CP patients into eight subgroups and calculated the PC risk.…”
Section: Cp and Pcmentioning
confidence: 99%